Epstein–Barr Virus Epithelial Cancers—A Comprehensive Understanding to Drive Novel Therapies - Han, Shuting; Tay, Joshua K.; Loh, Celestine Jia Ling; Chu, Axel Jun Ming; Yeong, Joe Poh Sheng; Lim, Chwee Ming; Toh, Han Chong (Frontiers in Immunology, 2021)
Epstein–Barr virus (EBV) is a ubiquitous oncovirus associated with specific epithelial and lymphoid cancers. Among the epithelial cancers, nasopharyngeal carcinoma (NPC), lymphoepithelioma-like carcinoma (LELC), and EBV-associated gastric cancers (EBVaGC) are the most common. The role of EBV in the pathogenesis of NPC and in the modulation of its tumour immune microenvironment (TIME) has been increasingly well described. Much less is known about the pathogenesis and tumour–microenvironment interactions in other EBV-associated epithelial cancers. Despite the expression of EBV-related viral oncoproteins and a generally immune-inflamed cancer subtype, EBV-associated epithelial cancers have limited systemic therapeutic options beyond conventional chemotherapy. Immune checkpoint inhibitors are effective only in a minority of these patients and even less efficacious with molecular targeting drugs. Here, we examine the key similarities and differences of NPC, LELC, and EBVaGC and comprehensively describe the clinical, pathological, and molecular characteristics of these cancers. A deeper comparative understanding of these EBV-driven cancers can potentially uncover targets in the tumour, TIME, and stroma, which may guide future drug development and cast light on resistance to immunotherapy.